Analisis Faktor Risiko Kejadian TB Paru Pada Keluarga Di Wilayah Kerja Puskesmas Malawili Kabupaten Sorong - Simon Lukas Momot; Maria Loihala; Yehud Maryen; Panel Situmorang (Jurnal Keperawatan Florence Nightingale, 2026)
Pulmonary tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis and remains a major public health concern. This study aimed to analyze the risk factors associated with the occurrence of pulmonary TB among families in the working area of Malawili Public Health Center, Sorong Regency. An analytical observational study with a cross-sectional design was conducted. The study included 35 families, consisting of 6 pulmonary TB case families and 29 non-case families, selected using a total sampling technique. Data were collected through structured questionnaires and observation checklists and were analyzed using the Chi-square test at a significance level of α = 0.05. The results revealed significant associations between pulmonary TB occurrence and residential density (p = 0.005), household ventilation (p = 0.017), and health practices (p = 0.022). In contrast, no significant associations were found for knowledge level (p = 0.079), household lighting (p = 0.061), and access to health information (p = 0.086). It can be concluded that environmental factors, particularly residential density and household ventilation, as well as health practices, are associated with the occurrence of pulmonary TB among families. Therefore, improving housing environmental conditions and strengthening healthy practices should be prioritized as part of pulmonary TB prevention and control efforts within the community.